A novel process for direct solvent regeneration via solar thermal energy for carbon capture. (April 2017) - Khalilpour, Rajab; Milani, Dia; Qadir, Abdul; Chiesa, Matteo; Abbas, Ali
Abstract: The energy for the solvent regeneration of post-combustion carbon capture (PCC) process is typically provided by steam bleeding from the power plant (PP) steam cycle. The energy penalty for steam bleeding results in serious reduction in the PP capacity estimated to be in the range of 10–40%. Power plant repowering or hybridization using solar-assisted PCC (SPCC) is a promising approach to satisfy carbon capture targets as well as PP load, concurrently. The drawback of this methodology is that notable amounts of solar energy are wasted during heat transfer from solar radiation to rich solvent. This paper presents a novel approach by eliminating the costly desorber system and using solar collector pipe (i.e. parabolic trough pipe) to directly heat the rich solvent and disassociate the bonds of CO2 -solvent. This novel technology lowers the process capital expenditure, and also reduces the solvent regeneration energy bringing it close to its theoretical values. The elimination of the complex desorber column also increases the flexibility of the PP operation in response for market dynamics. A case-study for Sydney-Australia shows that in comparison with SPCC methodology, this state-of-the-art approach could notably improve the economics of the process and reduce the size of solar collector field (SCF). Highlights: A new concept for direct solvent regeneration in solar collectors is proposed. The typical desorber unit of the PCC is replaced by solar thermal pipes. The techno-economics of the new concept is compared with conventional PCC and SPCC. The solar collector field and solvent storage parameters are optimized and compared. A major reduction in solar field size and an increase in annual benefit is reported.